Assessing the societal adoptability of participatory water management: an application of the Motivation and Ability (MOTA) framework. Issue 5 (9th July 2021) - Sadik, Md Shibly; Hermans, Leon M.; Evers, Jaap; Nguyen, Hong Quan; Khan, Malik Fida A.; Ahmed, Sadiq
Abstract: Exploring whether society is sufficiently equipped and motivated to adopt planned interventions is vital for modern plan development trajectories. The Motivation and Ability (MOTA) framework offers a tool to assess the societal adoptability of plans by exploring stakeholders' motivations and abilities. It was originally developed to assess plan implementation feasibility for structural measures of flood management in the Mekong Delta. Further development is necessary before applying the tool in other contexts and for other types of planning interventions. Institutional measures like participatory water management (PWM) have long been recognized as essential elements for water management, but have so far also remained out of the reach of conventional planning assessment tools such as cost–benefit or cost-effectiveness analyses. This research, therefore, aims at extending the MOTA tool in the context of PWM reforms in Bangladesh. It does this by, first, further detailing the MOTA components and identifying indicators for quantification and, second, an expert validation and application of this framework for coastal communities in Bangladesh. Our results suggest that the MOTA framework is capable of informing policymakers and implementing agencies about how to enhance the stakeholders' motivation and ability to ensure an enduring implementation of PWM reforms. HIGHLIGHTS The Motivation and Ability (MOTA) framework appeared recently to capture the societal and institutional dimensions in assessing the implementation feasibility of structural measures. This research further extends the MOTA framework and tests whether this can be applicable in case of assessing the implementation feasibility of soft measures like participatory water management. Graphical Abstract